2020
DOI: 10.1177/0040517520975660
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the water-based polyurethane with acrylate terminal process in nylon fabrics application using the Taguchi-based gray relational analysis method

Abstract: This study synthesized the water-permeable and hydrophobic property of water-based polyurethane (WPU) and applied it to nylon fiber-based functional textiles. Specifically, poly-stearyl acrylate (PSA) homopolymers with different molecular weights were used as end-capping agents in the WPU to form water-based polyurethane with acrylate terminal (WPUA). In the WPUA process, dimethylacetamide was adopted as a neutralizing agent to form a stable WPUA emulsion. The effects of the design parameters, such as the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The analysis of variance (ANOVA) 27,28 is used to evaluate the experimental error and confirm the influence of each factor on the significant factors in the product process. The control factors of the melt-spinning process include nanographene content, mold temperature, metering pump speed, melting temperature, hot roll speed and take-up speed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis of variance (ANOVA) 27,28 is used to evaluate the experimental error and confirm the influence of each factor on the significant factors in the product process. The control factors of the melt-spinning process include nanographene content, mold temperature, metering pump speed, melting temperature, hot roll speed and take-up speed.…”
Section: Methodsmentioning
confidence: 99%
“…The Taguchi method [23][24][25][26][27][28] used an orthogonal array to design experiments to study the influence of the control factors. The signal-to-noise (S/N) ratio is employed to analyze the experimental data to find the optimum parameter for each quality.…”
Section: Taguchi Methods Experiments Designmentioning
confidence: 99%
See 2 more Smart Citations
“…WPUA exhibits the advantages of both constituent polymers, and many studies have investigated optimizing the properties of WPUA as a coating material. 11,12 For example, Deng et al demonstrated the effect of the polyurethane/polyacrylate ratio on the properties of WPUA hybrid emulsions and films. 13 Although WPUA shows considerably enhanced performance in flexible and hard coatings, for applications under harsh conditions, other properties such as acid resistance, thermal stability, and electric insulation need to be further developed.…”
Section: Introductionmentioning
confidence: 99%